The problem of identification of Belarusian scientific schools in the field of humanities and social sciences - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2026)
The article considers the problems of identifying and describing Belarusian scientific schools in the field of humanities and social sciences based on lexicography, science studies, sociology and philosophy. The existing definitions of the concept «scientific school» and the types of scientific schools are analysed. The features of institutionalisation of certain scientific schools (the Minsk school of science studies and the Minsk methodological school) are revealed. The experience of implementing the state programme to support leading scientific schools of Russia based on scientific schools in the field of lexicography, sociology and philosophy is studied. The following scientific schools are described taking into account the criteria for identifying leading scientific schools in Russia identified in the scientific literature: 1) schools of Belarusian lexicography (the Minsk school of dialectal lexicography, the Minsk school of historical lexicography, the Minsk school of etymological lexicography, the Gomel school of author’s lexicography); 2) schools of Belarusian sociology (Belarusian sociological school, school for the analysis of social conflicts and disasters, school of economic sociology and sociology of labour, school in the field of science studies and sociology of science, school of the theory and methodology of sociological research and sociology of the social sphere); 3) school of Belarusian philosophy (the Minsk school in the field of philosophy and methodology of science). The authors conclude that there are a number of general criteria by which the presence of a scientific school in a given field of scientific knowledge is determined, and that in the field of lexicography, in addition to general criteria, there are specific requirements for emerging scientific schools.
Keywords: scientific school; typology of scientific schools; institutional analysis of the characteristics of scientific schools